Development of soybean host plant resistance and other management options for the stem borer, Dectes texanus leconte - Niide, Terutaka (Kansas State University, 2009)
Several studies were conducted to develop soybean management options that could provide protection from the soybean stem borer, Dectes texanus LeConte. Selected soybean genotypes were screened for host plant resistance against D. texanus. Soybean plants were grown in a footprint that could be covered by a field cage. When beetles were flying in the fields they were collected and placed in the field cages to increase the insect feeding pressure on the test plants. A susceptible commercial soybean variety treated with the systemic insecticide fipronil was used as a positive antibiosis check. Both commercial soybean varieties and plant introductions (PIs) obtained from the USDA National Soybean Germplasm Collection in maturity groups (MG) VI to VIII were tested over a four-year period. Since the number of ovipositions per plant could not be controlled, the ratio of oviposition punctures (OP’s) per live larvae (OP/ Lv) was used as a novel index of potential plant antibiosis to D. texanus. Field evaluations identified PI165673 as a genotype with a very high OP/ Lv ratio - similar to that for the fipronil antibiosis control. PI165673 appears to be potential source of resistance to D. texanus. Factorial analysis indicated that soybean maturity group was not significant factor in the expression of resistance. The OP/ Lv ratio appears to be more sensitive means of identifying antibiosis than other more conventional damage indices. The use of field cages demonstrated consistent plant responses from year to year during the multi-year study. Greenhouse-grown soybean plants, including transgenic plants containing the Manduca sexta chitinase gene, were not morphologically appropriate for successful D. texanus oviposition because the greenhouse-grown plants were poorly developed and had not produced enough pith in petioles. Therefore the greenhouse results were inconclusive. Analysis of the vertical distribution of D. texanus oviposition on soybean plants revealed that D. texanus oviposition was most likely to occur on leaf petioles on the upper five nodes of the plant canopy. Histomorphological observations of plant petioles indicated that the proportion of the petiole perimeter occupied by vascular bundles might be related to D. texanus oviposition. Both foliar and seed applications of fipronil suppressed D. texanus larval damage on soybean plants. The efficacy of these treatments was sustained for long periods, even until adult beetles were present in early August. The effects of the fipronil seed-treatment and harvest date on grain yield were both significant while the interaction was not. A physiological yield loss of 8.2% and plant lodging losses of 2.9% were associated with D. texanus infestation.
Keywords: Dectes texanus; Soybean plant introduction; OP/ Lv ratio; fipronil; soybean grain yield; Agriculture, Agronomy (0285); Agriculture, General (0473)